Prices Regulation in the Fuel Market in Argentina (1989-2015): From the Free Market to an Oligopolistic Structure (2020)
The economic crisis of the late 1980s implied a structural change in the Argentine economy of which the hydrocarbon complex was not exempt. In this framework, the objective of the article is to analyze what the neoliberal reform proposals were, how they were implemented and what was the impact on the dynamics of the fuel market considering its morphology, the price dynamics and the quantities produced, both during the nineties as after the crisis of the convertibility and the beginning of a new process in the hydrocarbon complex with price regulation. For this, the study contemplates the use of qualitative collection and analysis techniques that allow to survey and analyze the declarations of the main political and economic actors, as well as quantitative techniques through the processing of official national and international statistics.